THE USE OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD IN TEACHING STUDENTS' READING NARRATIVE TEXTS (A Quasi Experimental Study on the Eighth Graders of SMPN 40 Bandung) - Nery Eka Pratiwi, - (2008)
The study is entitled "The Use of Cooperative Integrated Reading and Composition (CIRC) Method in Teaching Students' Reading Narrative Texts. The purposes of the study are to investigate whether the use of CIRC method could give significant improvement between experimental and control groups upon reading achievement and to investigate students' response of the use of CIRC implementation. The study employed a quasi experimental design with two groups of the eighth graders of SMPN 40 Bandung participated in the study, experimental group (N=30) and control group (N= 30). The instruments used were test and interview. The test consisted of a set of multiple choice questions with pretest and posttest design while the interview was focused on advantages and disadvantages of CIRC, students' obstacles faced during the treatments, and their strategies to reduce their obstacles from students' point of view The results indicated that there was statistically significant difference between experimental and control groups with marginally better (p < 0.05) on dependent variable. It was proved by the data which were analyzed by parametric t-test sample in SPSS 17.00 for windows. Moreover, the findings from interview data revealed that the students gave positive responses of CIRC implementation. The students enjoyed the classroom activities because they recognized that CIRC method helped them to understand the texts easier, helped to develop relationship (Johnson and Johnson, 1994; Gillies, 2002; Patrick, 2007), and encouraged them to learn English initiatively (Stevens, Madden, Slavin & Farnish, 1989). However, the study also included suggestions and recommendations